Penentuan Kapasitas dan Lokasi Optimal dari PV Hosting Pada Penyulang Patin di Gardu Induk Metro - Osea Zebua; Zulmiftah Huda; Ubaidah Ubaidah; Noer Soedjarwanto (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2026)
The increasing capacity of solar power plants connected to the electric distribution network can cause disruptions to the operation of the electric distribution network. Therefore, the maximum capacity of PLTS installed on the electric distribution network or PV hosting must be evaluated and determined. This paper aims to determine the maximum capacity and optimal location of PV hosting on the electric distribution network with a case study on the Patin feeder at the Metro Substation. The operational limitations used in the evaluation of determining the maximum capacity of PV hosting include line overloading, overvoltage on the bus, overloading of the power transformer and reverse active power to the power transformer. The optimal location is the bus where the PV hosting with the maximum capacity is placed which results in the minimum power losses. Determination of the maximum capacity and optimal location of PV hosting on the Patin feeder was carried out by simulation using MATLAB software. The simulation results show that the maximum capacity of PV hosting on each bus in the Patin feeder ranges from 0.093-3.078 MW. Most of the maximum capacity values ​​of PV hosting on each bus are obtained by achieving violations of the reverse active power constraints. The optimal location for PV hosting placement is on bus 10 with an active power loss of 7.51 kW..